LINKAGE CHARACTERISTIC OF SMES TO ENTREPRENEURIAL ORIENTATION, CUSTOMERS, COMPETITORS, INNOVATION, COMPETITIVE ADVANTAGE TO IMPROVE PERFORMANCE IN SMES IN CENTRAL JAVA - Darmanto - (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Food is a necessity for the people of Indonesia is no exception Surakarta society. The growth of the quantity of food industry in Surakarta very high but growth is very low quality. Competition among the industry is very tight so it requires a strategy that can win the competition.The purpose of this study to analyze the effect of food on the characteristics of SMEs entrepreneurial orientation, customers, competitors, innovation, competitive advantage. This influence can be used to optimize the performance of the organizationThis study population food industry in Surakarta. With convenience sampling method determined 625 samples. Methods of analysis used cross-analysis (Cros Tab)The results of this research are gender, education, experience, and age orietasi significant positive effect on customers, competitors. Gender, education, experience, and age significant positive effect on entrepreneurship, but gender had no effect. Men and women have a level of entrepreneurial orientation is no different. Education, experience, and age orietasi significant positive effect on innovation, gender has no effect. Men and women have the same level of innovation orientation, gender, education has no effect on the competitive advantage while the experience, and the positive effect signafikan age. Gender, education, experience, and age significant positive effect on the performance of SMEsKeywords: Entrepreneurship, Customer, Competitor. Innovation, Performance Marketing